Knowledge, Attitudes of Mothers, and Mothers’s Participation in Pregnant Mother Class in Working Area of Sidodadi Public Health Center Bengkulu - Yuni Rahmadhaniati; Elza Wulandari; Rida Wahyuni (Jurnal Sains Kesehatan, 2019)
Class of pregnant women is a study group of pregnant women with gestational age between 20 weeks to 36 weeks (before delivery) with a maximum number of participants of 10 people. This study aims to study the relationship between knowledge and attitudes of mothers with the participation of classes of pregnant women in the Sidodadi Public Health Center Working Area in Central Bengkulu Regency. This study used a cross sectional design. The population in this study were third trimester pregnant women who lived in the Sidodadi Public Health Center Working Area in June 2018 as many as 58 pregnant women. Taking sample cases using the Total Sampling technique is that all pregnant women in the third trimester who live in the Sidodadi Public Health Center Working Area as many as 58 pregnant women are sampled. The results were obtained: (1) there were 24 with a percentage of 41.4% who did not take classes in pregnant women and 34 people with a percentage of 58.6% who attended classes in pregnant women; (2) there are 19 pregnant women with a percentage of 32.8% who lack knowledge, there are 22 pregnant women with a percentage of 37.9% who have sufficient knowledge and there are 17 pregnant women with a percentage of 29.3% who are well-informed; (3) there are 26 pregnant women with a percentage of 44.8% who do not support, and there are 32 pregnant women with a percentage of 55.2% who support; (4) There was a significant relationship between knowledge with the participation of pregnant women with a moderate relationship category; (5) There was a significant relationship between the attitude of mothers and the participation of classes of pregnant women with the category of moderate relationships. It was recommended to Sidodadi Public Health Center to further improve health services, provide health related information during pregnancy and encourage pregnant women to take part in pregnancy exercises.] Keywords: class of pregnant women, knowledge, mother's attitude